1996
DOI: 10.1021/bc960007z
|View full text |Cite
|
Sign up to set email alerts
|

Protein Patterning with a Photoactivatable Derivative of Biotin

Abstract: A method is described for the covalent immobilization of macromolecules at defined location on polymer surfaces. A thin film of a photoactivatable analogue of biotin, N-(4-azido-2-nitrophenyl)-N'-(N-d-biotinyl-3-aminopropyl)-N'-methyl-1,3- propanediamine (photobiotin, in salt form) was dried onto polystyrene or nitrocellulose surfaces and then exposed to intense white light through a mask to yield patterns of biotin covalently bound to the polymers. The subsequent addition of avidin resulted in the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 14 publications
1
61
0
3
Order By: Relevance
“…[79][80][81][82] Masked light exposure and incubation with streptavidin generated streptavidin patterns that were used for assembly of target biotinylated proteins at selected surface concentrations controlled by the exposure dose. Alternatively, biotin was site-selective reacted with chemical patterns obtained by masked irradiation or laser scanning of surfaces modifi ed with caged coupling agents,…”
Section: Caged Ligands and Photocleavable Tags For Generating Complexmentioning
confidence: 99%
“…[79][80][81][82] Masked light exposure and incubation with streptavidin generated streptavidin patterns that were used for assembly of target biotinylated proteins at selected surface concentrations controlled by the exposure dose. Alternatively, biotin was site-selective reacted with chemical patterns obtained by masked irradiation or laser scanning of surfaces modifi ed with caged coupling agents,…”
Section: Caged Ligands and Photocleavable Tags For Generating Complexmentioning
confidence: 99%
“…Depending upon the nature of the surface coating and the structure of the fusion protein this approach could offer immobilisation methods that are extremely mild, potentially reversible and with the opportunity to control the orientation of the immobilised biomolecules. We have recently described a method for photopatterning surfaces with biotin (Hengsakul & Cass, 1996) and this could be readily used with streptavidin or avidin-binding sequences fused to the protein that is to be immobilised. One such sequence has been described (Schmidt & Skerra, 1993) which contains ten amino acids (SAWRHPQFGG), X-ray crystallographic (Schmidt et al, 1996) studies have revealed that it is the sequence HPQ that is the primary recognition site by streptavidin, and titration calorimetry has been used to investigate the binding of such sequences to streptavidin in solution (Schmidt et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The two main methods are photolithography 9,46,55,66 and direct photochemical patterning. 9,26,68 In photolithography, a positive photoresist layer is spin-coated onto the substrate, exposed to UV light through a photomask and then developed to form micrometer sized open regions where adhesionpromoting molecules are bound (Figure 20(a)). The substrate is then immersed in solvent to remove the remaining photoresist, and adhesion-resistant molecules are bound to the exposed glass surfaces.…”
Section: Photochemistry-based Printingmentioning
confidence: 99%